The Influence of Income Inequality, Gross Domestic Product Open Unemployment Rate, and Education on Crime Rates in All Regency Lampung - Andromeda, Gilar Cahya; Marselina, Marselina; Yulihar Taher, Arivina Ratih (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2024)
High crime rates are often associated with social and economic problems such as income inequality, unemployment, low education, and inequality in development between regions. This study aims to analyze the effect of income inequality, open unemployment rate (OUR), education (GPR), and gross regional domestic product (GDP) on crime rates in Lampung Province from 2019 to 2022. Using a quantitative approach with a correlational design and secondary time series data per district or city, the analysis was conducted through multiple linear regression and typology. The results of the study showed that the four variables had a significant effect on crime. The cities of Bandar Lampung, East Lampung, and Central Lampung are noted for having high levels of inequality and crime. The local government is expected to focus more on equitable development and addressing social issues, such as unemployment and access to education, to reduce crime rates.